2012
DOI: 10.9734/ejmp/2012/1062
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Erythrocytic Membrane Free Energy of Albino Rabbits Administered Ethanol Leaf Extract of Spondias mombin Linn

Abstract: Aims:To determine the effect of ethanol extract of Spondias mombin Linn on membrane potential energy, the intracellular and extracellular concentrations of Na + , K + , Ca 2+ and Mg 2+ in an easily accessible model cell, erythrocyte, was studied. The effect on the first approximation estimates of erythrocytic free energy changes (∆G) was calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The ionic current that maintains this resting membrane potential of cells and the changes that occur in response to the presence of a disease condition, pharmacologic or signaling molecules constitute the complex electrophysiologic network that controls the pathophysiological process of any given disease, the contractile activity of smooth muscle, signal transduction of a nerve cell, among others. 29,30 The results of this study (Table 2) showed that neither pre-eclampsia nor pregnancy significantly affected the calculated free energy changes associated with divalent cation transport. This observation could be attributed to the absence of certain subcellular organelles such as sarcoplasmic reticulum and plasmalemma in erythrocytes which are necessary for storage of these cations, especially calcium, within cells.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The ionic current that maintains this resting membrane potential of cells and the changes that occur in response to the presence of a disease condition, pharmacologic or signaling molecules constitute the complex electrophysiologic network that controls the pathophysiological process of any given disease, the contractile activity of smooth muscle, signal transduction of a nerve cell, among others. 29,30 The results of this study (Table 2) showed that neither pre-eclampsia nor pregnancy significantly affected the calculated free energy changes associated with divalent cation transport. This observation could be attributed to the absence of certain subcellular organelles such as sarcoplasmic reticulum and plasmalemma in erythrocytes which are necessary for storage of these cations, especially calcium, within cells.…”
Section: Resultsmentioning
confidence: 69%
“…Unlike the other cations studied, a negative erythrocyte membrane free energy was obtained for calcium which corroborated similar observation with normal erythrocytes from albino rabbits. 29 This indicates that membrane free energy studies using changes in calcium concentrations may offer better empirical evidence than the use of the other divalent cations. Interestingly, the negative membrane free energy values obtained using calcium was not affected by both pre-eclampsia and pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Alkaloids are a class of plant-friendly compounds. They are useful for warding off parasites and predators [38] and have also been shown to have anti-asthmatic, anticancer, and antimalarial properties [39] .While alkaloids can be toxic, they have been shown to have vasodilatory, antihyperglycemic, cholinomimetic, antiarrhythmic [40], antimicrobial, and analgesic characteristics [41,42] . Tannins are important secondary metabolites of plants with different medicinal importance.…”
Section: Discussionmentioning
confidence: 99%
“…Serum sodium was estimated by the colorimetric method outlined by Igwe et al (2020). Briefly, 1.0 ml of filtrate reagent was pipetted into test tubes labeled as blank, standard, and sample.…”
Section: Estimation Of Serum Sodium Concentrationmentioning
confidence: 99%